Prevalence Of Entamoeba Spp. Among Aboriginal School Children In Kuala Kubu Bharu, Selangor - Noradilah, S.A.; Mohamed Kamel, A.G.; Hasan, Z. A.; Majid, R.; Mansur F.A.F. (Fakulti Sains Kesihatan, Universiti Kebangsaan Malaysia, 2024)
Volume :3 No:2